Peak Oxygen Consumption Scaled to Body Composition Is Associated With Mortality and Morbidity in People With a Fontan Circulation - Curtis A. Wadey; Alan R. Barker; A. Graham Stuart; Dan‐Mihai Dorobantu; Guido E. Pieles; Derek L. Tran; Karina Laohachai; Julian Ayer; Rob G. Weintraub; Rachael Cordina; Craig A. Williams (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Peak oxygen consumption (peak V̇$$ \dot{V} $$O2) is traditionally scaled by body mass, but it is most appropriately scaled by fat‐free mass. However, it is unknown whether peak V̇$$ \dot{V} $$O2 scaled by fat‐free mass is associated with mortality and morbidity in people with a Fontan circulation. The aim of this study was to assess the associations between different expressions of peak V̇$$ \dot{V} $$O2 with mortality and morbidity in people with a Fontan circulation. Methods and Results Eighty‐seven participants (aged 24.1±7.3 years; 53% women) with a Fontan circulation completed a cardiopulmonary exercise test and a dual‐energy x‐ray absorptiometry scan. Cox proportional hazard regressions models assessed the association (hazard ratio [HR]) between different expressions of peak V̇$$ \dot{V} $$O2 with a composite outcome of Fontan failure (FF). Participants were followed up for a median of 6.5 years (95% CI, 6.4–6.9). Individuals experiencing FF (n=10/87) had a significantly lower absolute peak V̇$$ \dot{V} $$O2. In univariable models, peak V̇$$ \dot{V} $$O2 ratio scaled to body mass was not significantly associated with FF (HR, 0.91; P=0.111). However, peak V̇$$ \dot{V} $$O2 scaled by fat‐free mass (HR, 0.90; P=0.020) or lean mass (HR, 0.90; P=0.017) was significantly and inversely associated with FF. These associations remained significant after adjusting for age, sex, and peak respiratory exchange ratio. Conclusions The association between peak V̇$$ \dot{V} $$O2 and FF is improved when scaled to measures of body composition. Applied clinically, a 1‐unit increase in peak V̇$$ \dot{V} $$O2 scaled to fat‐free mass or lean mass is associated with a ≈10% lower risk of FF.